Pojęcie wolności i jego teoretyczne konotacje - Kopinska, Violetta (Kultura-Społeczeństwo-Edukacja, 2012)
There do exist two basic approaches towards the term ‘freedom’. The first one, is a general approach, related to an universal meaning of the term. The second one, is a particular approach, based on taking/heading for understanding of freedom in plural terms. Both approaches might, but not necessary do, exclude each other. An alternative takes an interpretation of particular freedoms, which simultaneously excludes the existence of a universal freedom (and the other way around). On the other hand, conjunction, i.e. the examination of a universal freedom on the basis of analysis of particular freedoms and/or reconstruction of the term “freedom” on the basis of interpretations and meanings given to particular freedoms. As a follower of the idea of conjunction of both approaches, I’m analyzing in this paper the theoretical connotations of this term such as: the feeling of freedom, its limitations, responsibility, tolerance, auto-creation and self-realization. This is being done for the reason to stress out the depth and the vastness of freedom, as well to let the potential reader reconstruct it.